2012
DOI: 10.22409/engevista.v15i1.417
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação Da Produtividade Do Processo De Soldagem Mag Por Simulação Com O Método De Hipercubo Latino

Abstract: Resumo: O objetivo deste trabalho é o estudo da viabilidade da utilização do Método de Simulação pelo Hipercubo Latino na estimativa da produtividade do processo de soldagem elétrica MAG em obras de montagem de tubulações industriais com base em pequenas amostras. O estudo foi realizado a partir da análise de dados históricos em obras realizadas na REDUC (Refinaria Duque de Caxias -Estado do Rio de Janeiro -Brasil), onde foi utilizado o software ControlTub 5.3 na coleta dos dados. A partir desta base de dados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…These results were not expected. It showed that the lower the diameter, the higher the level of challenge of execution of a welded joint (Martins, 2011; PROMINP, 2009). There are no evidences in this study that explain these occurrences.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These results were not expected. It showed that the lower the diameter, the higher the level of challenge of execution of a welded joint (Martins, 2011; PROMINP, 2009). There are no evidences in this study that explain these occurrences.…”
Section: Resultsmentioning
confidence: 99%
“…Some improvements were expected, at least from the tenth day onwards. This is because of the familiarisation of workers with the environment and working conditions (Martins, 2011; PROMINP, 2009; Pellegrino et al. , 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Os ambientes de desenvolvimento de modelos de simulação a eventos discretos podem ser definidos como ferramentas computacionais que auxiliam a análise de problemas, que vão de logística e manufatura até redes de computadores, sem recorrer a modelos analíticos de teoria das filas (Peixoto et al, 2013); (Martins, 2013).…”
Section: Introductionunclassified